Powder mixing - Kaye, Brian H. (Brian Howard) (Powder technology series., 1997)
The operation of a powder mixer requires a knowledge not only of the mixing mechanisms but of the physical properties of the powders being mixed. Kaye explores the physics of powder systems including characterisation procedures and rheology.